DIGITAL LITERACY ON THE PEDAGOGICAL COMPETENCE OF ELEMENTARY SCHOOL TEACHERS - Ni Luh Putu , Karina Dewi; Putu, Sanjaya; I Made, Sedana (Universitas Islam Negeri Mataram, 2026)
This study aims to examine the influence of digital literacy on the pedagogical competence of elementary school teachers in Sayung District, Demak Regency. The research employed a quantitative, ex post facto design. The population consisted of elementary school teachers in Sayung District, with 177 teachers participating as respondents. Data were collected using a five-point Likert-scale questionnaire to measure digital literacy and pedagogical competence. The digital literacy instrument covered technical skills, cognitive abilities, and evaluation of digital information content, while the pedagogical competence instrument included understanding students’ characteristics, curriculum development, instructional implementation, assessment and evaluation, and the utilization of learning technology. The instruments were tested for validity and reliability before data collection. Data were analyzed using descriptive statistics and simple linear regression after fulfilling the prerequisite assumptions. The results revealed a strong positive correlation between digital literacy and pedagogical competence (r = 0.796, p < 0.05). Regression analysis showed that digital literacy significantly influences pedagogical competence (F = 303.194, p < 0.05), with a coefficient of determination (R²) of 0.634. This indicates that digital literacy accounts for 63.4% of teachers’ pedagogical competence. The regression equation Y = 64.631 + 1.070X demonstrates a positive relationship between the variables. These findings highlight the importance of strengthening teachers’ digital literacy to enhance pedagogical competence in the context of educational digital transformation